Coexistence of DVB-T2 and 5G in The Low-Band Frequency: Performance Analysis Using SEAMCAT Simulator - Rina Amaelia; Soni Joyo Saputra; Deni Alva Reza; Alfin Hikmaturokhman; Solichah Larasati (JURNAL INFOTEL, 2026)
The development of telecommunications technology in Indonesia is driving the increased demand for high-speed data services, one of which is through the implementation of 5G networks. The Indonesian government has established the use of the low band 700 MHz frequency band, which is adjacent to the digital television service frequency DVB-T2, specifically 478–694 MHz. This condition has the potential to cause interference between systems. This study analyzes the probability of interference between 5G services and DVB-T2 using SEAMCAT based on the Monte Carlo (MC) method with the Okumura-Hata propagation model. The simulation results show that the farther the distance between the transmitter and the DVB-T2 receiver, the lower the probability of interference tends to be. At a transmission power of 30 dBm, a minimum distance of 10 km is required to reduce the probability of interference to 1%. Additionally, higher transmission power increases the risk of interference, especially at close distances. Therefore, appropriate frequency management strategies and power level determination must be implemented to optimize the 5G rollout without disrupting DVB-T2 services, especially in areas with high transmitter density.